La Valeur Per#xE7;ue Du Microcr#xE9;dit Comme D#xE9;terminant De La Satisfaction Des Clients Des Institutions De Microfinance : Une Etude Sur La Client#xE8;le Des EMF Au Cameroun (Global Journal of Management and Business Research, 2019)
The purpose of this article is to evaluate the perceived value of the microcredit offer as a major determinant of the satisfaction of clients of Microfinance Institutions in Cameroon. So, a study was conducted in the microfinance sector in Cameroon, with 367 EMF clients. The results obtained show that the perceived value of the microcredit offer, through its two dimensions, namely the perceived benefits derived from the use of the microcredit offer and the perceived costs of obtaining microcredit, plays a role major in the formation of customer satisfaction.
Keywords: satisfaction; perceived value; microcredit; microfinance; establishment of microfinance